1984
DOI: 10.1159/000118087
|View full text |Cite
|
Sign up to set email alerts
|

Altered Distribution of T Lymphocyte Subsets in Lithium-Treated Patients

Abstract: 37 lithium-treated patients, 6 prelithium patients and 12 healthy volunteers were studied regarding relative and absolute numbers of peripheral blood lymphocytes, T lymphocytes and T lymphocyte subsets defined with monoclonal antibodies (OKT4, OKT8). Prelithium patients did not differ significantly from healthy volunteers. The relative and absolute numbers of OKT4 cells were lower in lithium-treated patients than in the controls. The relative number of OKT8 cells increased with increasing duration of lithium t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Lithium has been demonstrated to have a consistent positive effect on lymphocyte-based host de fense systems [6], such as enhancing T-lymphocyte sub sets, T4T8 ratios, following administration in normal patients and those receiving lithium for manic depressive psychoses [6]; enhancing T-lymphocyte-derived colonystimulating activity through an effect upon T-suppressor cells [7]; and elevating the circulating granulocytes in clin ical conditions such as cyclic neutropenia [8][9][10] and con genital and acquired neutropenia [11][12][13]. It appears throughout many of the clinical studies performed that for lithium to be effective in neutropenic patients depends on the presence of a residual stem cell population capable of responding to lithium.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium has been demonstrated to have a consistent positive effect on lymphocyte-based host de fense systems [6], such as enhancing T-lymphocyte sub sets, T4T8 ratios, following administration in normal patients and those receiving lithium for manic depressive psychoses [6]; enhancing T-lymphocyte-derived colonystimulating activity through an effect upon T-suppressor cells [7]; and elevating the circulating granulocytes in clin ical conditions such as cyclic neutropenia [8][9][10] and con genital and acquired neutropenia [11][12][13]. It appears throughout many of the clinical studies performed that for lithium to be effective in neutropenic patients depends on the presence of a residual stem cell population capable of responding to lithium.…”
Section: Introductionmentioning
confidence: 99%
“…The criteria for a diagnosis of depression were not stated in terms of RDC or DSM-111, and the medication status of the patients at the (13), using RDC criteria for major depression, found melancholic patients to have lower mitogen responses than controls, but the study lacked age-and sexmatched controls studied on the same day as the patients. Krueger et al (12) found decreases in the percentage of T-cell number and in T-cell function in patients who met DSM-111 criteria for major depression, but 5 of the 6 patients studied were o n psychotropic medicines known to alter immune function (16,21,29). This study also evaluated NK activity, and reported no significant change between depressed and control groups.…”
Section: Discussionmentioning
confidence: 75%
“…Concomitantly, lithium elevates the concentration of circulatory TNF-α (Beyaert, Schulze-Osthoff, Roy, & Fiers, 1991;El-Twab & Abdul-Hamid, 2016;Matsebatlela, Gallicchio, & Becker, 2012). This elevation might be attributed to the activation of the extracellular signal-regulated kinase (ERK) pathway (Kim et al, 2012;Sung et al, 2019), mitogen-activated protein kinases (MAPK)-ERKdependent pathway (Hull et al, 2014), nuclear factor-kappa B (NF-κB)-independent pathway (Schotte, Loo, Carpentier, Vandenabeele, & Beyaert, 2001;Sung et al, 2019), protein kinase C (PKC) (Young, Wang, Woods, & Robb, 1999), CD4 helper T-cell/CD8 suppressor (Wahlin, Knorring, & Roos, 1984) or initiation of granulocytosis (Kleinerman, Knowles, Blick, & Zwelling, 1989). Thus, lithium stimulates TNF-mediated cytotoxicity (Gallicchio, Hughes, Tse, Ling, & Birch, 1995).…”
Section: T a B L E 4 Maternal Administration Ofmentioning
confidence: 99%